Pengembangan Modul Ajar Problem Based Learning (PBL) pada Materi Peluang di Kelas X SMA Assa’adah Bungah Gresik - Masruroh, Baiti; Kurniawati, Yeva (EDUKASI, 2024)
The purpose of this research is to produce a product in the form of a teaching module by utilizing a problem-based learning model, namely problem-based learning by focusing on feasible opportunity material by considering 3 aspects, namely valid, practical, and effective. This development research model uses the 4D model, which includes 4 stages namely define, design, develop, and disseminate. This research was conducted in the even semester of the 2023/2024 academic year at SMA Assa'adah Bungah. The results of the research that has been carried out, prove that the teaching module produced is declared valid by getting a score of 3.3, which puts it in the valid category. The teacher response questionnaire scored 3.1, which placed it in the practical category, and the learner response questionnaire scored 3.7, which placed it in the very practical category. In addition, three observers found that the analysis of the learning implementation sheet was effective with an average score of 94% for the fully implemented category and through the summative test results obtained an average score of 90 for the very effective category. Since all three aspects of the teaching module assessment have been met, the teaching module is suitable for use.